THE EFFECT OF TEACHING STYLES AND THE MOTOR EDUCABILITY TO SERVE UNDER MINI VOLLEYBALL (EXPERIMENTAL STUDY AT MIN MEDAN) - Yusuf . (Journal Physical Education, Health and Recreation, 2016)
This study aims to determine the effect of teaching styles and the motor educability to serve under mini volleyball at MIN Medan.In addition, this study also aimed to determine the effect of motor educability of both the teaching style. Teaching style in this study are the inclusion of teaching style and teaching of command style also high educability motor and low educability motors.Reseach carried aout in Class V MIN Medan academic year 2014-2015 (even semester). The research method is experimental design with treatment by the level of 2x2 with a sample of 76 students.The results of this study are as follows: (1) overall there are significant differences between the teaching styleof inclusion with teaching style command to increased volleyball servicing. (2) There is an interaction between teaching style with a motor educability to increased volleyball servicing. (3) For students who have a high educability motors, wich are taught by the teaching style inclusion is better than teaching style command to increased volleyball servicing. (4) There is no difference between teaching style inclusion with teaching style command for student who have a lower educability motors in volleyball service improvement.